The Effect of Green Tea EGCG (Epigallocatechin Gallate) Clinical Benefit Pocket Book Education on Knowledge Level of D4 Anesthesiology Nursing Students, Universitas Muhammadiyah Purwokerto - Annisa, Rully -; Cing, Marta Tania Gabriel Ching; Budiyanti , Nur Aini (Jurnal Ilmu Kesehatan, 2024)
Increased knowledge can be supported by improving education delivery methods in health education, so that the quality of health services will also increase. The pocket book method is a simple way or tool used to increase student knowledge with health education (education) methods. Epigallocatechin Gallate (EGCG) is the main polyphenolic constituent found in green tea and contributes 50% to 80% which represents 200 to 300 mg/cup of green tea. Design: Quasi-Experiment with Non-Equivalent One-Group Pretest-Posttest Design. Methods: The method used in this study is a Quasi-Experiment with a Non-Equivalent One-Group Pretest-Posttest Design . The number of respondents was 58 second semester students with the Simple Random Sampling Technique . Data collection used a Knowledge Level questionnaire which was used to measure the level of knowledge before and after the intervention . Data analysis using Paired Sample T Test. Results: The results of the statistical test showed that most of the respondents (70.7 %) had sufficient level of knowledge before being given the intervention, while 10 students had less knowledge (17.2%). Furthermore, after receiving the intervention, most of the respondents had a good level of knowledge, namely as many as 36 students (62.1 % ). Conclusions: Pocket Book Education The Clinical Benefits of Green Tea EGCG ( Epigallocatechin Gallate ) in increasing the level of knowledge is very effective because the pocket book method is a simple way or tool used to increase student knowledge with health education (education) methods . This activity is also intended to be able to increase knowledge in using medicinal plants appropriately and rationally.